STUDI PEMETAAN PERILAKU (BEHAVIORAL MAPPING) PEJALAN KAKI PADA PEDESTRIAN ALUN-ALUN KOTA LAMONGAN - Hammam Rofiqi Agustapraja (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
Aloon-aloon of Lamongan area is the area that became the center of the crowd in Lamongan. This area is very strategic because it can be reached by all walks of life from various parts of the city. Pedestrian in Aloon-aloon of Lamongan experienced a change of function at night that is as a center of street hawkers, thus making pedestrian rights become reduced. The existence of various kinds of problems make the function of the pedestrian and the convenience of pedestrian activity is not running properly. from this research is to know the pattern of pedestrian behavior in Area of Aloon-Aloon of Lamongan based on existing rules and regulations. Data analysis uses qualitative analysis which is used to explain the result of survey which conducted in Area of Aloon-aloon of Lamongan about public response to pedestrian. The results of this study are expected to provide future input on the development of pedestrian both in terms of function and comfort so that the pedestrian line functions properly as an open space that should be used for pedestrian activity so that the creation of comfort for users, and impact on the image of a pedestrian-friendly City.